2020
DOI: 10.1016/j.stemcr.2020.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Mechanical Analysis of Human Pluripotent Stem Cell-Derived Cardiomyocytes for Drug Testing and Pathophysiological Studies

Abstract: Summary Current platforms for studying the mechanical properties of human pluripotent stem cell-derived cardiomyocytes (hPSC-CMs) as single cells do not measure forces directly, require numerous assumptions, and cannot study cell mechanics at different loading conditions. We present a method for directly measuring the active and passive forces generated by single-cell hPSC-CMs at different stretch levels. Utilizing this technique, single hPSC-CMs exhibited positive length-tension relationship and ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Measurements of contractility have been widely used for research on both adult and neonatal myocytes ( Belostotskaya and Golovanova, 2014 ; Berger et al., 1994 ; Boudreau-Béland et al., 2015 ; Harary and Farley, 1960 ; Haworth et al., 1987 ; Hissa et al., 2017 ; Jesus et al., 2020 ; Penitente et al., 2014 ; Ramadan et al., 2018 ). More recently, human induced pluripotent stem cell-derived CMs (hiPSC-CMs) have been employed as a model for human cardiac disease and drug screening ( Ballan et al., 2020 ; Birket et al., 2015 ; Gong and Sobie, 2018 ; Lahti et al., 2012 ; Lan et al., 2013 ; Ribeiro et al., 2015 ; Wang et al., 2014 , 2019 ). The development of this new experimental model, although showing great promise, also brings some challenges to efficiently detect CM contraction dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Measurements of contractility have been widely used for research on both adult and neonatal myocytes ( Belostotskaya and Golovanova, 2014 ; Berger et al., 1994 ; Boudreau-Béland et al., 2015 ; Harary and Farley, 1960 ; Haworth et al., 1987 ; Hissa et al., 2017 ; Jesus et al., 2020 ; Penitente et al., 2014 ; Ramadan et al., 2018 ). More recently, human induced pluripotent stem cell-derived CMs (hiPSC-CMs) have been employed as a model for human cardiac disease and drug screening ( Ballan et al., 2020 ; Birket et al., 2015 ; Gong and Sobie, 2018 ; Lahti et al., 2012 ; Lan et al., 2013 ; Ribeiro et al., 2015 ; Wang et al., 2014 , 2019 ). The development of this new experimental model, although showing great promise, also brings some challenges to efficiently detect CM contraction dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…However, varying inotropic effects have also been reported. Measuring from single-cell hiPSC-CMs, Ballan et al (2020) reported 11% increase in force at 100 nM but higher doses, 1 and 10 µM, suppressed contractility. Ribeiro et al (2017) , also measuring single-cell hiPSC-CMs, reported positive inotropy immediately after administration of 100 nM omecamtiv mecarbil.…”
Section: Discussionmentioning
confidence: 97%
“… 110 Moreover, relevant non‐myocyte cardiac cells such as vascular, cardiac fibroblasts, epicardial and endocardial precursor cells could also be generated, allowing to construct more clinically relevant cardiac‐like structures and asses the role of non‐myocyte/cardiomyocyte crosstalk in cardiac pathologies. Similarly, ongoing efforts are focused on enhancing hiPSC‐CM maturation through the use of thyroid and glucocorticoid hormones, 111 the effects of extracellular‐matrix and tissue‐engineering strategies, mechanical and electrical training, changes in the metabolic fuel to free fatty acids, and other interventions.…”
Section: Opportunities To Intervene – a New Toolboxmentioning
confidence: 99%